Elasto-plastic modeling of saturated and non-saturated residual soil with parameters optimization - Singh S.; Prasad A. (My University, 2025)
Engineering properties of bentonite soils get modified upon contamination with different chemicals from industrial waste. Bentonite soil is often used as a material for clay liner. But its engineering properties change when it is contaminated. To see the effect of inorganic & organic chemical on bentonite soil, two chemicals (Aluminum hydroxide and Acetic acid) that are generally found in municipal solid waste were selected. The effect of these chemicals on Bentonite soil has been studied in a controlled condition in the laboratory. The optimum values of these chemicals are evaluated and added separately to Bentonite soil. The engineering properties such as Differential Free Swell, Hydraulic Conductivity and Swelling Pressure were found out. The result of differential free swell indicate that with Acetic acid and Aluminum hydroxide the free swell decreases by 47% and 49% respectively. The hydraulic conductivity results show that it decreases by 12% with Aluminum hydroxide and 17% by Acetic acid. Tests were also carried out to evaluate Shear strength parameters of Bentonite soil upon contamination with chemicals. The result of swelling pressure indicated that it decreased by 82% when Aluminum Hydroxide was added and increased by 20% when Acetic Acid added was added, Maximum Dry Density decreased by 14.8% when Aluminum hydroxide was added & 7% with Acetic acid, The strength parameters cohesion 'c' and the angle of internal friction (Ø) were also evaluated and was observed that cohesion decreases by 50% with Aluminum Hydroxide and 43% with Acetic Acid, and angle of internal friction almost remain same. The selected soil is considered to be highly expansive in nature. In addition to these tests some test were also carried out to study the fabric of soil such as Scanning Electron Microscope (SEM), Cation Exchange Capacity (CEC), Infra-Red Spectroscopy (IR), X-Ray Diffraction (XRD) and Specific Surface Area.